INTEGRASI MATERIAL PAMOR KERIS DAN STRUKTUR VISUAL MEGA MENDUNG DALAM PERANCANGAN PERHIASAN KONTEMPORER BERBASIS KUNINGAN - Ceni Magaline; Arif Mawaskito; Maharani Dian Permanasari (Jurnal Riset Multidisiplin Edukasi, 2026)
This study is a design-based research aimed at exploring the integration of keris pamor as a cultural material and the stylization of the Mega Mendung batik motif as a visual structure in the design of brass-based contemporary jewelry. The novelty of this research lies in the integration of pamor material and Mega Mendung stylization into a unified jewelry design concept. The method employed is design thinking, consisting of the stages of empathize, define, ideate, and prototype. The results produce jewelry prototypes that integrate cultural material and visual structure within a single design construction. This study proposes a culture-based design approach that positions culture not merely as ornamentation but as a conceptual system in contemporary jewelry design.